2001
DOI: 10.1046/j.1439-0523.2001.00624.x
|View full text |Cite
|
Sign up to set email alerts
|

Heterosis for yield and other agronomic traits of winter triticale F1 and F2 hybrids

Abstract: Triticale is generally treated as a self‐pollinating crop and line breeding is practised. Hybrid breeding has been discussed for some time, but there is little information for winter triticale. This study investigated heterosis for eight agronomic traits in F1 and F2 hybrids grown together with their parents as drilled plots in three environments. On average, grain yield heterosis was 12.5 dt/ha (a relative 10.5%) compared with the mid‐parent value for F1 hybrids, and 6.2 dt/ha (5.0%) for F2 hybrids and withaw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
11
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 6 publications
9
11
0
1
Order By: Relevance
“…Fischer et al (2010) mention that the prediction of the heterosis based on the parents averages of a single cross result in low precision, and in such a case, it would be advisable to carry out a general and specific combining ability analysis. Other authors (Oettler et al 2001;Cifci and Yagdi 2007;Yildirim et al 2014) have reported similar values of heterosis and heterobeltiosis in triticale. Traits that presented inbreeding depression were SP (-21.6), SL (-2.52), SS (-3.29), SG (-5.99) and GY (-26.64).…”
Section: Resultsmentioning
confidence: 52%
“…Fischer et al (2010) mention that the prediction of the heterosis based on the parents averages of a single cross result in low precision, and in such a case, it would be advisable to carry out a general and specific combining ability analysis. Other authors (Oettler et al 2001;Cifci and Yagdi 2007;Yildirim et al 2014) have reported similar values of heterosis and heterobeltiosis in triticale. Traits that presented inbreeding depression were SP (-21.6), SL (-2.52), SS (-3.29), SG (-5.99) and GY (-26.64).…”
Section: Resultsmentioning
confidence: 52%
“…Information regarding the amount of heterosis in relation to grain yield and other agronomic traits is yet scarce for winter crops. Results from experiments with individual Triticale plants, or in small plots, have been published (Grzesik and Węgrzyn 1998;Oettler et al 2001;Yildririm et al 2014). The present study was carried out using a diallel cross system among five genotypes of Triticale to assess the general and specific combining abilities and to discriminate the best F1 parents and hybrids that express superior heterosis.…”
Section: Diallel Analysismentioning
confidence: 99%
“…Published papers mention Mh with values of 4.4 to 17.7% (Oettler et al 2001), -2.9 to 20.5% (Oettler et al 2003) and -11.4 to 22.4 % (Oettler et al 2005), while Yildirim et al (2014) obtained values ranging from -11.72 to 30.36%. According to Oettler et al (2003), the results from singleplant experiments or small plots tend to overestimate heterosis.…”
Section: Grain Yieldmentioning
confidence: 99%
See 1 more Smart Citation
“…Полагают, что данная культура обладает большим потен-циалом проявления гетерозиса, чем пшеница, вследствие того, что в состав ге-нома тритикале входит набор хромосом ржи, который обусловливает склонность к перекрестному опылению (Oettler et al, 2005). Анализу проявления гетеро-зисного эффекта у тритикале посвящен ряд работ, в которых прослеживается наличие гетерозиса при скрещивании как яровых, так и озимых форм (Pfeiffer et al, 1998;Oettler et al, 2001;Goral et al, 2005;Fischer et al, 2010). Показано, что гетерозис может с успехом применяться для повышения урожайности и улучшения отдельных компонентов качества зерна тритикале.…”
Section: Introductionunclassified